Laterally Positioned Flap: A Simple and Successful Technique to Cover Isolated Recession of Miller Class-I - Chaudhary, Shashi Kant; Shah, Harish Kumar; Goel, Khushboo; Shrestha, Sajeev (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Gingival recession is a common mucogingival deformity that brings aesthetic discomfort, hypersensitivity and inability to perform proper oral hygiene. LPF is the widely used technique to cover single recession of Miller Class-I and Class-II when adequate keratinized tissue exists adjacent to the recession. We report a case of 32-year-old female who presented with chief complaints of receding gum and sensitivity in lower front teeth region. Clinical examination revealed Miller’s Class-I vertical recession with 4 mm depth on buccal aspect of left mandibular canine. LPF was planned and operated for the root coverage. After 6 months of therapy, 100% root coverage was achieved with satisfactory healing and aesthetic was comparable to adjacent gingiva.